Revitalizing Qur'anic Learning Centers through the Integration of Islamic History: A Community Engagement Approach to Strengthening Children's Islamic Character - Imroatul Istiqomah; Tri Yuliana Wijayanti; Mohamad Syafiq Musyafa; Adha Eka Rahmadhani; Ahmad Iqbal Syauqi; Hizbullah Rasyid (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2026)
Daaru Thulab Qur'anic Learning Center (TPA), located at Ar-Rahmah Mosque, has traditionally focused its instruction on Qur'anic literacy, Islamic ritual practices (ibadah amaliyah), and the memorization of daily prayers. However, Islamic history has not been systematically incorporated into the curriculum, despite its significant potential to foster the internalization of Islamic values and strengthen students' character development. This community engagement program aimed to revitalize learning at the Qur'anic Learning Center through the integration of Islamic history into instructional activities to strengthen the Islamic character of students by promoting exemplary values derived from the life of Prophet Muhammad SAW., his Companions, and prominent Muslim scholars. The program employed three main strategies: the development of an Islamic history teaching module, professional training for Qur'anic Learning Center teachers, and the direct implementation of learning activities by student volunteers from the University of Darussalam (UNIDA) Gontor during the Community Service Program (Kuliah Kerja Nyata, KKN). The findings indicate that students developed a deeper understanding of influential figures in Islamic history, while teachers demonstrated greater confidence in delivering lessons using more engaging themes and instructional approaches. The proportion of students achieving the minimum learning mastery increased substantially from 39.3% before the intervention to 78.6% after its implementation. These findings suggest that integrating Islamic history into non-formal Islamic education not only enhances students' cognitive understanding of Islamic civilization but also contributes significantly to strengthening their Islamic character.